2009
DOI: 10.1074/jbc.m109.032888
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine Insufficiency Caused by Aging and Overnutrition Compromises Mitochondrial Performance and Metabolic Control

Abstract: In addition to its essential role in permitting mitochondrial import and oxidation of long chain fatty acids, carnitine also functions as an acyl group acceptor that facilitates mitochondrial export of excess carbons in the form of acylcarnitines. Recent evidence suggests carnitine requirements increase under conditions of sustained metabolic stress. Accordingly, we hypothesized that carnitine insufficiency might contribute to mitochondrial dysfunction and obesity-related impairments in glucose tolerance. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
342
5
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 291 publications
(374 citation statements)
references
References 65 publications
25
342
5
2
Order By: Relevance
“…Previous studies have identified numerous metabolic regulatory proteins as targets for repression by miR-378 and miR-378* (10,(26)(27)(28). In addition, we found that carnitine O-acetyltransferase (CRAT), a mitochondrial enzyme involved in fatty acid metabolism (29,30), and MED13 are repressed by miR-378 and miR-378*, respectively. Our findings indicate that miR-378 and miR-378* function to control the overall oxidative capacity of metabolically active tissues during periods of dietary stress.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Previous studies have identified numerous metabolic regulatory proteins as targets for repression by miR-378 and miR-378* (10,(26)(27)(28). In addition, we found that carnitine O-acetyltransferase (CRAT), a mitochondrial enzyme involved in fatty acid metabolism (29,30), and MED13 are repressed by miR-378 and miR-378*, respectively. Our findings indicate that miR-378 and miR-378* function to control the overall oxidative capacity of metabolically active tissues during periods of dietary stress.…”
mentioning
confidence: 65%
“…4A). CRAT channels the products of β-oxidation to the TCA cycle, away from mitochondrial efflux, thereby coupling mitochondrial fatty acid uptake to oxidative metabolism (29,30,39). Reduced CRAT activity has been identified as a reversible abnormality of the metabolic syndrome (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these LCAC metabolites were significantly higher in HFrEF than HFpEF, inversely related to LVEF. As a reflection of impaired or dysregulated FAO, the elevated plasma LCAC observed may suggest a shared metabolic impairment of the HF clinical syndrome independent of LVEF 13, 53, 54. Given that FAO impairments or dysregulation may result from a variety of mitochondrial insults, further investigation will be needed to identify the causal processes underlying the LCAC elevations reported in this study 12, 83.…”
Section: Discussionmentioning
confidence: 88%
“…Functionally, they facilitate transfer of LCFAs into the mitochondria for ß‐oxidation 52. Although typically short‐lived, LCAC accumulate in states of inefficient fatty acid oxidation (FAO), which may be attributed to (1) defects in mitochondrial FAO enzymes or (2) increased FAO relative to tricarboxylic acid (TCA) flux; this leads to a bottleneck of carbon substrates at the TCA cycle 53, 54. Such defects can be caused or exacerbated by IR, which has, in turn, been associated with elevations in plasma LCAC 54, 55, 56, 57.…”
Section: Discussionmentioning
confidence: 99%